HOAKS COVID 19 DAN LITERASI DIGITAL PEMERINTAH - Syarifah Kusumadewi Kinanggi; Muh. Akbar; Muhammad Farid (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
It is undeniable that it has had a negative impact on people's lives, both in terms of health, as well as political, economic, social, and so on. This made the government then issue several handling policies, including Enforcement of Restrictions on Community Activities, implementation of health protocols, including various rules in the order of religious life, one of which is an appeal to carry out worship at home. So that people can immediately know and comply with these rules, of course, we need an appropriate communication strategy by paying attention to the role of an opinion leader. Bulukumba Regency, South Sulawesi Province, which is the location of this research, is an area that has regulations on religion. Therefore, a religious figure can be said to be an opinion leader who has a strategic position, especially in communicating government policies related to Covid 19 on religious issues. This is in line with the two-step model of communication flow, both in the pattern of face-to-face communication and mass communication, which introduced the concept of an opinion leader. This research method is descriptive and qualitative with the aim of providing an overview of the role of religious leaders in public communication. Through the interview process with the Chairperson of the Indonesian Ulema Council and the Young Dai of Bulukumba Regency, it is known that public communication carried out by religious leaders is delivered through direct da'wah or using digital media. Furthermore, of course, the results of this research are expected to be an input for the government, in considering and determining opinion leaders in public communication on other issues.